Brain Based Learning Using Media Crossword Puzzle Enhances Students Understanding of Concepts and Thinking Skills - I Gusti Ngurah Oka Wiantara; I Gede Astawan; Ndara Tanggu Renda (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of brain based learning models assisted by crossword puzzles on the understanding of concepts and critical thinking skills in science. This research is a quasi-experimental study (quasi-experimental), with a non-equivalent post-test only control group design. The population of this study was the entire class V of SDN Cluster VIII Buleleng District in the academic year 2019/2020 consisting of 5 classes in five elementary schools with 129 students. Samples were taken with a random sampling technique of 2 classes. Data on understanding concepts and critical thinking skills in science is collected using the test method in the form of an essay test. Data were analyzed with the MANOVA test using SPSS 17 for Windows. The results showed that 1) there was a positive influence on the brain based learning model with the help of crossword puzzles on the understanding of the science concept (F count of 276,585; sig = 0,000 <0.05); 2) there is a positive influence of the brain based learning learning model assisted by the crossword puzzle media on critical thinking skills in science (F count is 238,963; sig = 0,000 <0.05); 3) there is a positive influence on brain based learning models assisted by the crossword puzzle media on the understanding of concepts and critical thinking skills in science (F count of 231.064; sig = 0.0001 <0.05). The brain based learning model with the help of crossword media can be applied to science learning in elementary schools as an effort to increase students' understanding of concepts and critical thinking skills maximally in science lessons.